Exploring the Anti-Inflammatory Effects of Aprepitant: An Antagonist of the Neurokinin-1 Receptor - J, Pavithra; G, Shila; P, Maheshwaran; M, John Staines; S, Sakthi Sundaram (Asian Journal of Biological and Life Sciences)
Aim: Substance P participates towards pain aetiology by activating on the NK-1R, the neurokinin-1 receptor, which is found on sensory neurons that perceive noxious stimuli. SP is recognised to have biological action through G-protein-coupled neurokinin receptors named Neurokinin 1 Receptor (NK-1R), Neurokinin 2 Receptor (NK-2R) and neurokinin 3 receptors (NK-3R). Among the three, NK-1R has the highest affinity for substance P. The NK-1R receptor is a G-protein-coupled receptor that is involved in inflammatory disorders. Aprepitant is a highly selective non-peptide neurokinin-1 receptor antagonist that is approved to lessen nausea and vomiting brought on by chemotherapy. Materials and Methods: The purpose of this study is to see if Aprepitant has any anti-inflammatory activity in the cotton pellet granuloma technique. Pellets with granuloma tissue around them were carefully dissected, cleared of extraneous tissues, and dried at 60ºC at the end of the research. Under both moist and dry circumstances, and each particle’s surrounding granuloma tissue’s mean weight was determined. Results: The study’s goal is to evaluate the anti-inflammatory impact and Aprepitant prevents granuloma formation (48.68%) at a dose of 80 mg/kg to the conventional medicine indomethacin (2.5 mg/kg), which demonstrated the maximum suppression of granuloma tissue development (55.34%). Conclusion: When compared to a control without an ulcerogenic impact, the histology of granuloma in aprepitant treated group tissue indicated considerable prevention of necrosis and exudates.
Keywords: Aprepitant; Chronic inflammation; Cytokines; Neurokinin 1 receptor; Substance P